KINERJA GURU SEJARAH DALAM PEMBELAJARANDARINGDI SMA N 6 SAROLANGUN JAMBI - Dewi Mutiara Sari; Suroyo Suroyo; Yuliantoro Yuliantoro (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract:. The research purposed to know the history teachers’ performance indicators while online learning at SMAN 6 Sarolangun Jambi. The research method of this research is descriptive quantitative by using survey method. The Technique of data collection of this research used questionner as instrument. Then, the technique of data analysis used descriptif statistical using presentation. The population of this research were 346 students of SMAN 6 Sarolangun Jambi. The result of history teacher performances indicators while covid 19 pandemic was medium score.Key Word: Teachers’ performance indicator, online learning, history